An Investigation into Self-Translation - Maklakova, Natalia Vasilevna; Khovanskaya, Ekaterina Sergeevna; Grigorieva, Leona L. (Journal of History Culture and Art Research, 2017)
The paper analyzes the nature, basic aspects, and specific features of self-translation in the context of translation theory and practice, as well as basic causes making writers translate their works. The analysis of the works on the topic shows that the issue is understudied and demands further investigation. Our analysis shows that self-translation (translation of the author) is considered to be the translation of an original work into another language by the author himself. On the one hand, it is a rather rare phenomenon. On the other hand, self-translation represents “ideal” translation since the author is in a better position than any ordinary translator because he knows his creation as nobody else and has the authority to allow himself shifts in the translation which might not have been ‘allowed’ by another translator. The results of self-translation can be regarded as certain “gold standards” for others to make use of. There are different reasons that cause bilingual writers to translate their works, both linguistic (interest to languages, wish to create and use new expressive means, dissatisfaction with existing translations, etc.) and extra-linguistic (emigration, challenge to check one’s gift in new conditions, paying tribute to motherland, etc.). It is obvious that some reasons are objective, but others can be considered subjective, the latter being more powerful and stimulating.